Designed Molecular Space in Material Science and Catalysis - Shirakawa, Seiji; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2018)
This book focuses on molecular space chemistry, which is recognized as an important concept for the design of novel functional materials and catalysts. A wide variety of topics and ideas included in this book are based on that concept. The book showcases recent representative examples of molecular space design to create functional materials and catalysts possessing unique properties. This unique volume will be of great interest to chemists in a wide variety of research fields, including organic, inorganic, biological, polymer, and supramolecular chemistry. Readers will obtain new ideas and directions to create novel functional molecules, and those ideas will lead to innovative views of science. .
π-Electronic Ion-Pairing Supramolecular Assemblies -- Molecular Space Chemistry Based on Pillar[n]arenes -- Inherently Chiral Calix[4]arenes as Supramolecular Catalysts -- Synthesis of the Longest Carbohelicene by Multiple Oxidative Photocyclizations of Arylene-Vinylene Oligomers -- Design of the Chiral Environment for Asymmetric Acid-Base Catalysis -- Biaryl Amino Acids and Their Surrogates: A Unique Class of Unnatural Amino Acid -- Interplay of Diamides and Rare Earth Metals: Specific Molecular Spaces and Catalytic Activity -- Control of Chiral Molecular Space Using Helical Polymers -- Functional Supramolecular Materials Formed by Non-covalent Bond -- Photo-responsive Dynamic Molecular Catalyst for Spatiotemporal Control of Chemical Reactions -- Mimicking Integrated Functions of "Molecular Space" in Biological Systems by Using Crystalline Cavities Consisting of Short Peptides. .
Keywords: Nanochemistry; Catalysis; Nanotechnology; Chemistry, Organic; Nanochemistry; Catalysis; Nanotechnology; Organic Chemistry